A Scalable Smartwatch-Based Medication Intake Detection System Using Distributed Machine Learning. - Fozoonmayeh, Donya; Le, Hai Vu; Wittfoth, Ekaterina; Geng, Chong; Ha, Natalie; Wang, Jingjue; Vasilenko, Maria; Ahn, Yewon; Woodbridge, Diane Myung-kyung (Journal of Medical Systems, 2020)
Poor Medication adherence causes significant economic impact resulting in hospital readmission, hospital visits and other healthcare costs. The authors developed a smartwatch application and a cloud based data pipeline for developing a user-friendly medication intake monitoring system that can contribute to improving medication adherence. The developed Android smartwatch application collects activity sensor data using accelerometer and gyroscope. The cloud-based data pipeline includes distributed data storage, distributed database management system and distributed computing frameworks in order to build a machine learning model which identifies activity types using sensor data. With the proposed sensor data extraction, preprocessing and machine learning algorithms, this study successfully achieved a high F1 score of 0.977 with 13.313 seconds of training time and 0.139 seconds for testing.